SOSIO-CULTURAL ADAPTATION STRATEGIES OF NON-MAKASSARESE STUDENT IN ADDRESSING CULTURE AT THE FACULTY OF LANGUANGES AND LITERATURE UNM - Andi Hajar; Citra Dwi Safitri; Nayla Aulia Salsadila; Rahmat Alimuddin (Media Inovasi Pendidikan dan Publikasi, 2026)
This study aims to analyze the socio-cultural adaptation strategies of non Makassarese students in dealing with culture shock at the Faculty of Languages and Literature, State University of Makassar (FBS UNM). Non Makassarese students often experience difficulties in adapting to a new environment due to differences in language, social norms, interaction patterns, and culture. These conditions may lead to culture shock, which affects both social and academic adjustment. This study employs a qualitative approach using a descriptive method. Data were collected through interviews and observations of the students at FBS UNM. The collected data were analyzed to identify the forms of culture shock experienced by students and the socio-cultural adaptation strategies they use in adapting to a new environment. The results of this study are expected to provide an overview of the culture shock experienced by migrant students and the adaptation strategies they apply to adjust to the social and academic environment at the Faculty of Languages and Literature, State University of Makassar.